Laboratory and Theoretical investigations of Petroleum Reservoir Fluid Properties (American Journal of Energy and Natural Resources, 2022)
Understanding the Pressure-Volume-Temperature (PVT) properties is very important to many kinds of petroleum determinations like calculations of reservoir fluid properties; expect the future performance, selection of enhanced oil recovery methods, and for production facilities design. Models for expecting reservoir fluid properties has been increased attention during last decade by knowing reservoir pressure and temperature, oil API gravity, and gas gravity. In general, PVT properties are obtained from laboratory experiments but in some cases In this study, complete PVT lab experiments were done and evaluated the most frequently used empirical black oil PVT correlations for application in the Middle East. Empirical PVT Correlations for the Middle East crude oil was compared as a function of commonly available PVT data. Correlations compared for: Bubble point pressure, solution gas oil ratio, oil formation volume factor, oil density, and oil viscosity. After evaluating the Empirical correlations, the crude sample was characterized using different EOS to arrive at one EOS model that accurately describes the PVT behavior of crude oil produced. The multi-sample characterization method is used to arrive at one consistent model for crude oil for the whole reservoir. The fluid sample is first analyzed for consistency to ensure that they are representative of oil produced, then it is used to obtain parameters for EOS model. The tuning procedure for the EOS is done systematically by matching the volumetric and phase behavior results with laboratory results. Results showed that some correlations give good results in PVT properties compared to the laboratory and can be used with Libyan oil, while some give a high percentage of error.